Institutions at a crossroad: creative destruction or destructive creation? - Birzhenyuk, Grigory M.; Efimova, Tatyana V. (Journal of the Belarusian State University. Sociology, 2020)
We are witnessing and participating in a very dynamic and powerful process of changing many parameters that have been inherent in a number of social institutions for a long time and have been historically stable up to a certain point. These changes are largely due to the influence of sharing, a phenomenon that originated in the modern economy, has acquired intensive development in connection with the progress in the field of information technologies and has given rise to the phenomenon of «sharing culture». The ideology of access is intensively replacing the idea of ownership that has dominated for centuries. The younger generation is especially susceptible to this. The authors put forward the hypothesis that, on the one hand there’s the deinstitutionalization of traditional social practices, on another hand sharing can be seen not so much as a culture, but as a phenomenon that has the characteristics of a new social institution, a kind of mega-institution that changes traditional institutions: family, education, labor, consumption, property relations, etc.